Neutrophilia in severe asthma is reduced in Ormdl3 overexpressing mice. Issue 3 (8th February 2023) - James, Briana N.; Weigel, Cynthia; Green, Christopher D.; Brown, Ryan D. R.; Palladino, Elisa N. D.; Tharakan, Anuj; Milstien, Sheldon; Proia, Richard L.; Martin, Rebecca K.; Spiegel, Sarah
Abstract: Genome‐wide association studies have linked the ORM (yeast)–like protein isoform 3 (ORMDL3) to asthma severity. Although ORMDL3 is a member of a family that negatively regulates serine palmitoyltransferase (SPT) and thus biosynthesis of sphingolipids, it is still unclear whether ORMDL3 and altered sphingolipid synthesis are causally related to non‐Th2 severe asthma associated with a predominant neutrophil inflammation and high interleukin‐17 (IL‐17) levels. Here, we examined the effects of ORMDL3 overexpression in a preclinical mouse model of allergic lung inflammation that is predominantly neutrophilic and recapitulates many of the clinical features of severe human asthma. ORMDL3 overexpression reduced lung and circulating levels of dihydrosphingosine, the product of SPT. However, the most prominent effect on sphingolipid levels was reduction of circulating S1P. The LPS/OVA challenge increased markers of Th17 inflammation with a predominant infiltration of neutrophils into the lung. A significant decrease of neutrophil infiltration was observed in the Ormdl3 transgenic mice challenged with LPS/OVA compared to the wild type and concomitant decrease in IL‐17, that plays a key role in the pathogenesis of neutrophilic asthma. LPS decreased survival of murine neutrophils, which was prevented by co‐treatment with S1P. Moreover, S1P potentiated LPS‐induced chemotaxis of neutrophil, suggesting that S1P can regulate neutrophil survival and recruitment following LPS airway inflammation. Our findings reveal a novel connection between ORMDL3 overexpression, circulating levels of S1P, IL‐17 and neutrophil recruitment into the lung, and questions the potential involvement of ORMDL3 in the pathology, leading to development of severe neutrophilic asthma. Abstract : Severe asthma is associated with a predominant inflammation and high levels of interleuking‐17 (IL‐17), which plays a key role in their accumulation in the airways. Ormdl3 transgenic mice with reduced circulating levels of the bioactive sphingolipid metabolite sphingosine‐1‐phosphate (S1P) had reduced neutrophil infiltration and IL‐17 after LPS/OVA challenge. This study revealed a new connection between Ormdl3 overexpression, circulating levels of S1P, IL‐17, and neutrophil recruitment into the lung.